2018
DOI: 10.1111/ffe.12847
|View full text |Cite
|
Sign up to set email alerts
|

Ratcheting effect of reinforced graphite sheet with stainless steel insert (RGSWSSI) under cyclic compression at elevated temperature

Abstract: Ratcheting and creep of reinforced graphite sheet with stainless steel insert (RGSWSSI) are tested under cyclic stress‐controlled compression by a self‐designed clamp from 500°C to 600°C. The effects of insert type, temperature, stress amplitude, stress rate, creep, and loading sequence are considered. Results present that ratcheting deformations for RGSWSSI with 316‐L stainless steel tanged and bonded insert approach to each other and show little rate dependence, while they slightly increase with the incremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This indicates that the proposed model can be well used to predict the damage behavior considering the notch effect. Taking into consideration the important effect of notch geometry on the degradation of HDPE pipes, the shakedown and low fatigue behavior of notched and virgin HDPE pipes will be further tested and evaluated in the following based on the approaches published in previous works [35,36,37,38,39] obviously. Moreover, the burst pressure remarkably decreases with the increment of the notch depth ratio.…”
Section: Damage Model Of Hdpe Pipes With Various Notchesmentioning
confidence: 99%
“…This indicates that the proposed model can be well used to predict the damage behavior considering the notch effect. Taking into consideration the important effect of notch geometry on the degradation of HDPE pipes, the shakedown and low fatigue behavior of notched and virgin HDPE pipes will be further tested and evaluated in the following based on the approaches published in previous works [35,36,37,38,39] obviously. Moreover, the burst pressure remarkably decreases with the increment of the notch depth ratio.…”
Section: Damage Model Of Hdpe Pipes With Various Notchesmentioning
confidence: 99%
“…If a material is subjected to a cyclic stress with non-zero mean stress and the applied stress exceeds the yield surface, a cyclic accumulation of inelastic deformation, called material ratcheting, will take place [23]. The material ratcheting is usually tested by a homogeneous stress field and characterized by the evolution of back stress considering the kinematic hardening effect [24], [25], [26], [27]. However, the structural ratcheting is mainly caused by a inhomogeneously distributed stress field and the plasticity of material, which is usually described by EPP or RO models.…”
Section: Fig1 Load Histories Of the Pressurized Shellmentioning
confidence: 99%
“…Paul et al 28 also studied the microstructure change of DP steel under cyclic loading controlled by asymmetric stress, and found that grain orientation had little influence on the development of substructure compared with the test type. In addition, some scholars have studied the influence of stress ratio, 29 maximum stress, 30 temperature, 31 and other test parameters on ratchetting evolution. Sahu et al 32 investigated the effect of martensitic phase transformation on ratchetting behavior in austenitic stainless steel, but they only predicted that the volume fraction of martensitic would increase with the increase of deformation degree.…”
Section: Introductionmentioning
confidence: 99%